ANALISIS NUTRISI PAKAN IKAN BERBAHAN BAKU LIMBAH KULIT IKAN TUNA (Thunnus albacares) - Sugihastira Sugihastira; Tri Widayati Putri; Jawiana Saokani; Zul Khairiyah (Universitas Mataram, 2026)
This study aimed to analyze the nutritional content of fish feed made from tuna (Thunnus albacares) skin waste as an alternative to utilizing fishery waste into value-added products. The study was conducted by preparing feed with varying percentages of tuna skin added. The nutritional content, including moisture content, ash content, crude fiber, protein, and fat, was then analyzed using standard methods. The results showed that the addition of tuna skin increased protein and fat content, with the highest values found in the 40% tuna skin treatment (36.98% protein, 11.72% fat, 6.60% fiber, 11.35% moisture content, and 7.85% ash content). All parameters met fish feed quality standards (SNI 9043-4:2022). This indicates that tuna skin waste has the potential to be utilized as an economical and environmentally friendly fish feed additive, while supporting the sustainability of fish farming.